Uso de la plataforma virtual MOODLE y su influencia en el proceso de enseñanza aprendizaje del Circuito 01 del Distrito 09D11 - Fructuoso Arreaga, Nelly Yohanna (2022)
The Moodle virtual platform is one of the safe and friendly learning platforms that most educational institutions use to create personalized content of the pedagogical material provided to the student, so it is necessary to potentiate the variables of the object of study to achieve improvements in the teaching-learning process. The general objective was to determine the influence of the Moodle virtual platform and its influence on teaching-learning in the educational units of circuit 01 district 09d11. The research work is based on the design of a proposal for the use of the virtual platform with the purpose of improving the teaching-learning process in the educational units. The research methodology is descriptive, applied and non-experimental, with a mixed approach, correlational design and the use of the interview as an instrument that will help to know the opinions on the research topic. As a data collection technique, a survey was applied to the 57 teachers of the educational units of circuit 01 district 09D11. The tool used for statistical analysis was SPSS, which showed very significant values for the dimensions studied; the sample was selected probabilistically. It is concluded that the Moodle virtual classroom has a positive relationship in the teaching-learning process, data that are corroborated in the Spearman correlation analysis, an implementation model should be considered for virtual platforms that will improve academic performance.